Penerapan Gerakan Literasi Sekolah Pada Minat Baca Peseta Didik di MTSN 1 Kota Kediri - Fina Miftahul Fa'izatil Ulya; Betty Rahmawati (Sosaintek: Jurnal Ilmu Sosial Sains dan Teknologi, 2025)
The low level of reading literacy in Indonesia, as reflected in the results of PISA 2022, poses a serious challenge in the field of education, especially at the elementary and secondary levels. One strategic step to improve literacy is through the School Literacy Movement (Gerakan Literasi Sekolah, GLS). This study aims to analyze the implementation of GLS at MTsN 1 Kota Kediri and its impact on students' reading interest. The research employed a descriptive qualitative method with data collection techniques including semi-structured interviews, participatory observations, and documentation. The findings reveal that the implementation of GLS is carried out through three stages: habituation (such as 15 minutes of reading before lessons begin), development (such as strengthening reading corners and organizing literacy competitions), and learning, which integrates literacy into the teaching and learning process. This implementation has had a positive effect on increasing students' reading interest, supported by the presence of professional teachers, adequate infrastructure, and parental involvement. Challenges faced include the limited collection of reading materials and the lack of engagement from some parents. This study provides a comprehensive overview of GLS implementation as an effort to enhance the culture of literacy in madrasahs